Genetic structure and admixture between the Posavina and Croatian Coldblood in contrast to Lipizzan horse from Croatia - A. Galov; K. Byrne; T. Gomerčić; M. Duras; H. Arbanasić; M. Sindičić; D. Mihelić; A. Kovačić; S.M. Funk (Czech Journal of Animal Science, 2013)
The Posavina and Croatian Coldblood are Croatian autochthonous horse breeds with interwoven breeding histories for which studbooks have only recently been established. The Lipizzan breed has the oldest formalized breeding and no record of recent genetic introgression from other breeds in Croatia. We analyzed the genetic structure, interbreeding, and breed characteristics by genotyping nine dinucleotide microsatellite loci for 53 Posavina, 37 Croatian Coldblood, and 33 Lipizzan horses and showed that differing breeding schemes and histories have had a strong and measurable impact on the population genetic structure within and between the three breeds. A Bayesian clustering method demonstrated that two population clusters best explain the genetic structure. Samples from the pre-defined breeds of the Posavina and Croatian Coldblood were assigned to a separate genetic cluster, while Lipizzan specimens were assigned to another distinct genetic group. Twelve samples of the Posavina/Croatian Coldblood cluster (13%) showed admixed ancestry with Lipizzan horses. A test for heterozygosity excess, allele frequency distribution mode-shift, and M-ratio test were used to detect genetic evidence of recent population bottlenecks, none of which provided evidence for bottlenecks in the Posavina and Croatian Coldblood populations. In contrast, although somewhat ambiguous, evidence suggests a genetic bottleneck in the Lipizzan population in Croatia.